The blended wing body (BWB) aircraft configuration - Dieter Scholz (Die Blended Wing Body (BWB) Flugzeugkonfiguration, 2010)
The Blended Wing Body (BWB) configuration has a potential to reduce weight, if a single shell design is applied (8% better). It has a better glide ratio, L/D (10% to 15% better). However, this was not apparent from the scale model AC20.30. There is a potential for a reduction in fuel consumption (mostly due to better L/D) and hence also a reduction in emissions. A reduction in noise can only be achieved with engines on top. Increase of airport capacity is possible, if an aircraft for more than 750 passengers is designed. The aircraft will probably not have problems with wake turbulence. Direct Operating Costs (DOC) will benefit mostly from the scale effect (larger aircraft). But: There are open certification issues. The BWB has an unstable configuration, ditching is not solved, rotation on take-off needs to be further investigated and landing gear integration is difficult.
Keywords: Preliminary Sizing; Aerodynamics; Wind Tunnel; Flight Mechanics; Structures; Mass Prediction; System Integration; Ground Handling; Emergency; Wake Turbulence; Air Transport System; Interior Design; BWB; Blended Wing Body